STUDENTS’ VOCABULARY MASTERY BEFORE AND AFTER TAUGHT USING TALKING STICK STRATEGY - Jusman Jusman; Ammang Latifa; Amaluddin Amaluddin (Universitas Muhammadiyah Makassar, 2021)
This exploration was expected to uncover that: to discover the understudies' vocabulary dominance previously, after educate through talking stick strategy, additionally the huge distinctive the understudies' vocabulary authority at the long term understudies of SMP Negeri 5 Pinrang. This examination utilized semi test strategy, with two gathering pre-test and post-test plan. The general population was the drawn out understudies of SMP Negeri 5 Pinrang. The example is picking by random sampling technic. Where, the specialist accept one class as trial class and one class as control class. The outcome of the data assessment showed that the understudies' jargon predominance improved through and through when given treatment. It was showed up by the mean score of the pre-test was (67.96) and the post-test was (78.70). It showed that talking stick strategy can improve the jargon authority of the drawn out understudies of SMP Negeri 5 Pinrang out and out. Resulting to inspecting the data by using t-test formula, the eventual outcome of t-test regard (4.58) and t-table (2.021), Those showed that H1 was recognized and H0 was excused.